Recent Progress on Low-Temperature Selective Catalytic Reduction of NOx with Ammonia - Park, Eun Duck (Molecules, 2024)
Selective catalytic reduction of nitrogen oxides (NOx) with ammonia (NH3-SCR) has been implemented in response to the regulation of NOx emissions from stationary and mobile sources above 300 °C. However, the development of NH3-SCR catalysts active at low temperatures below 200 °C is still needed to improve the energy efficiency and to cope with various fuels. In this review article, recent reports on low-temperature NH3-SCR catalysts are systematically summarized. The redox property as well as the surface acidity are two main factors that affect the catalytic activity. The strong redox property is beneficial for the low-temperature NH3-SCR activity but is responsible for N2O formation. The multiple electron transfer system is more plausible for controlling redox properties. H2O and SOx, which are often found with NOx in flue gas, have a detrimental effect on NH3-SCR activity, especially at low temperatures. The competitive adsorption of H2O can be minimized by enhancing the hydrophobic property of the catalyst. Various strategies to improve the resistance to SOx poisoning are also discussed.
Keywords: catalyst; low-temperature selective catalytic reduction of NO with NH3 (NH3-SCR); NOx reduction; SO2/H2O tolerance; transition metal-based catalysts